Growth characterization of Bacillus sp. strain ZEID-14 on acrylamide as the sole nitrogen source - Rahman, Mohd. Fadhil; Hanizam, Mohd Badrin; Abu Zeid, Isam M.; Shukor, Mohd Yunus (Hibiscus Publisher, 2022)
Acrylamide is a major pollution in soil from the breakdown of pesticides additive. Slowly but steadily, the use of microbe-mediated acrylamide breakdown as a bioremediation approach has gained attention all around the world. At room temperature, the effect of the initial pH on bacterial growth shows that the optimum pH range was discovered to be between 6.5 and 7.5. The optimal growing temperature at pH 7.5 ranged from 25 to 35 oC. In a series of experiments using a 1.0 percent (w/v) starting concentration of various organic carbon sources, it was determined that fructose, glucose and sucrose all supported the greatest amount of cellular growth on acrylamide. Acrylamide concentration of 500 mg/L promoted the most rapid expansion of growth, while levels of 1500 mg/L and higher entirely stopped growth. Mercury at 2 ppm caused 83% of inhibition whilst other metal ions such as copper, cadmium, lead and chromium showed minimal inhibition of less than 20% . The concentration of acrylamide and the time it took for this bacterium to start growing show an inverse relationship. A lag time of 1-3 days was found as the content of acrylamide was raised from 100 to 1000 mg/L while growth was abolished at 1500 mg/L. The maximal growth rate increased as acrylamide concentrations increased, indicating an overall trend of increased toxicity.